2015
DOI: 10.1111/ppc.12098
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Staff's Perceptions of Patient Safety in Psychiatric Inpatient Care

Abstract: The views of the nurses contribute to formalization of organizational policies and strategies. In particular, they highlight the importance of continual training for the staff and management, considering patients' views, and treating patients as collaborators in their care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 29 publications
0
27
0
6
Order By: Relevance
“…Safety in nursing practice constitutes protecting patients from harms arising from adverse events in care such as medication errors, poor communication in handover, insufficient staffing or inadequate education on new technologies (Sherwood, ). However, within mental health care, discussions of patient safety issues resulting from harms of the health care environment are limited (Kanerva, Lammintakanen, & Kivinen, ) and are often replaced by the notion of patient risk: the harms that a patient creates within the environment including violence, aggression, self‐harm or suicide (Bowers et al., ; Crowe & Carlyle, ; De Santis et al., ). In contrast to other hospital environments, within psychiatric inpatient settings, patient risk is conceptualized as affecting not only the individual, but also other patients, staff and the general public, widening the sphere of risk.…”
Section: Introductionmentioning
confidence: 99%
“…Safety in nursing practice constitutes protecting patients from harms arising from adverse events in care such as medication errors, poor communication in handover, insufficient staffing or inadequate education on new technologies (Sherwood, ). However, within mental health care, discussions of patient safety issues resulting from harms of the health care environment are limited (Kanerva, Lammintakanen, & Kivinen, ) and are often replaced by the notion of patient risk: the harms that a patient creates within the environment including violence, aggression, self‐harm or suicide (Bowers et al., ; Crowe & Carlyle, ; De Santis et al., ). In contrast to other hospital environments, within psychiatric inpatient settings, patient risk is conceptualized as affecting not only the individual, but also other patients, staff and the general public, widening the sphere of risk.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of PSC improves clinical practices; for example, the introduction of PSC has been linked to reductions in adverse events/errors (El‐Jardali, Dimassi, Jamal, Jaafar, & Hemadeh, ; Mardon, Khanna, Sorra, Dyer, & Famolaro, ; Robb & Seddon, ; Singer et al, ; Wang et al, ) and an improvement in certain clinician behaviours such as error reporting (Verbakel, Langelaan, Verheij, Wagner, & Zwart, ). In psychiatric care, culture has been identified as a critical patient safety factor (Kanerva, Lammintakanen, & Kivinen, ; True, Frasso, Cullen, Hermann, & Marcus, ; Vandewalle et al, ). Systematic reviews have found that healthcare organisations looking to improve PSC apply various strategies that directly involve the managers, including team‐based training programs, executive walk rounds, educational activities or training programs (Morello et al, ; Weaver et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Enhancing this understanding is necessary in order to support the potential of psychiatric nurses to facilitate the participation of patients in patient safety (Kanerva et al . ).…”
Section: Introductionmentioning
confidence: 97%
“…However, the empirical understanding of factors influencing this collaborative behaviour is limited in the context of care provided by psychiatric nurses. Enhancing this understanding is necessary in order to support the potential of psychiatric nurses to facilitate the participation of patients in patient safety (Kanerva et al 2014).…”
Section: Introduction Backgroundmentioning
confidence: 99%